Factors Influencing Purchase Intention for Luxury Brands in Indonesia’s Emerging Market - Teresia Debby; Atik Aprianingsih; Agus Hasan Pura Anggawidjaja; Wisnu Wardhono; Eric Angga Budiyono; Indi Rafiyal Ka’bah (Golden Ratio of Data in Summary, 2026)
The Indonesian luxury goods market has grown significantly over the past decade due to rising disposable incomes, urbanization, and a growing middle class. Understanding the drivers of luxury brands’ purchase intention is essential, especially in Generation Z. This study examines the influence of hedonic, social, and financial value on purchase intention through attitudes toward luxury brands among Generation Z in Indonesia. This study employs PLS-SEM to analyze data collected from 103 Generation Z respondents across Indonesia through an online survey. The results of this study indicate that financial value and hedonic value have a positive and significant influence on customer attitudes toward luxury brands, whereas social value does not have a significant influence on these attitudes. This finding indicates that consumers may prioritize intrinsic qualities of luxury items, such as quality and personal aesthetic appeal, over the social status associated with these goods. Additionally, customer attitude towards luxury brands has a positive and significant influence on purchase intention. The results of this study suggest that luxury brands in Indonesia can increase the purchase intention of Generation Z by fostering a positive attitude towards luxury brands, which offer both financial and hedonic value.